Parental education and delirium risk after surgery in older adults: A lifecourse analysis. (31st December 2021) - Arias, Franchesca; Chen, Fan; Shiff, Haley; Marcantonio, Edward R; Jones, Richard N; Travison, Thomas G; Schmitt, Eva M; Fong, Tamara G; Inouye, Sharon K
Abstract: Background: Delirium is common in older adults and is a risk factor for long‐term cognitive decline. Efforts to conceptualize risk factors for delirium have focused on the time period proximate to the episode, and the role of early‐life exposures on delirium risk is poorly understood. Social and historical factors interact with psychological and biological predispositions, particularly during critical and sensitive periods in childhood, to influence health across the lifespan. Understanding the association between early life exposures and acute conditions occurring after surgeries provides an innovative first step in applying cumulative lifecourse models to examine perioperative risks and outcomes. Method: Patients in the Successful Aging after Elective Surgery study, a cohort of adults 70+ scheduled for major non‐cardiac surgery, were interviewed prior to surgery to assess reading abilities. Cognitive functioning, neighborhood‐level characteristics, and medical co‐morbidities. Delirium incidence and severity were measured daily after surgery using the Confusion Assessment Method (CAM) and CAM‐severity (CAM‐S), respectively. Parental education and participation in cognitive stimulating activities were also assessed. Result: In our sample of 547 patients, higher paternal education was associated with significantly lower incidence of delirium (odds ratio OR = 0.93, 95% CI [0.87, 0.98]) and inversely associated with delirium severity (Spearman's rho = ‐.13, p < .001). Higher maternal education was associated with lower delirium incidence, but this association did not reach statistical significance. A multivariate model revealed that the effect of paternal education on delirium incidence was independent of the patient's education, the patient's verbal intelligence assessed pre‐operatively, medical comorbidities, neighborhood disadvantage, and participation in cognitively stimulating activities throughout the lifespan. Paternal education and general cognitive functioning at baseline explained about 10% of the variance in incidence of delirium (R 2 =.10, X 2 (7) =39.35, p<.001). Conclusion: Paternal education is associated with delirium severity and predicts delirium incidence independent of other delirium risk factors. A life course perspective examining early‐life exposures may yield unique insights into the risks and pathogenesis of delirium. More broadly, this study represents a novel exploration in the field of delirium, and our results contribute to the growing body of literature on the early‐life exposures associated with health in adulthood and will into older age.